Edukasi Cuci Tangan Pakai Sabun Menggunakan Media Permainan Hand’s Card pada Siswa Sekolah Dasar - Apriyanti, Dewi; Haris, Yuli Fathiyah; Ratnawati, A. Sri; Zahrany, Asyifa; Kurniawan, Nanang; Lalusu, Erni Yusnita; Rachmat, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2024)
A number of behavior-based illnesses are linked to inadequate soap handwashing. This demonstrates how important it is to practice hand washing with soap (HWWS). Teaching children to wash their hands with soap at a young age is the goal of this education program. Children in school are the ideal audience for HWWS promotion activities since they are receptive to new information and eager to share it with others. This activity used the educational game method with Hand's Card media (picture cards) and installation of HWWS poster. This service was conducted on January 13 and 14, 2023, at five public elementary schools (SDN) in Bonto Matene Village, South Sulawesi: SDN 26 Mangkaca, SDN 9 Mangkaca, SDN 34 Citta, SDN 1 Segeri, and SDN 2 Segeri. Students in Bonto Matene Village's grade 4 elementary school are benefiting from this activity, as seen by their excitement and participation in HWWS instruction, as well as by the notable changes of knowledge (p-value0.05) that occur both before and after education. It is anticipated that students will be able to put HWWS into practice in order to foster a HWWS culture that can enhance health.